Dietary lipid levels affect growth, feed utilization, lipid deposition, health status and digestive enzyme activities of juvenile Siberian sturgeon, Acipenser baerii. (3rd September 2021) - Ren, Yuanyuan; Wei, Shibo; Yu, Huanhuan; Xing, Wei; Xu, Guanling; Li, Tieliang; Luo, Lin
Abstract: A 10‐week experiment was conducted to evaluate the effects of dietary lipid levels on growth, feed utilization, lipid deposition, health status and digestive enzyme activities of juvenile Siberian sturgeon ( Acipenser baerii ). Six isonitrogenous diets were formulated with lipid levels at 51.1 (L5), 88.7 (L9), 129.6 (L13), 169.3 (L17), 208.4 (L21) and 248.8 g/kg (L25). The sturgeons fed with L17 had the highest growth and feed utilization. Higher dietary lipid obtained significantly lower PPV than that of L17 ( p < .05). Based on WGR, PPV, the optimal dietary lipid was estimated at 169.9, 176.0 g/kg. The lipid deposition in the whole body, muscle and liver enhanced significantly as the dietary lipid increased ( p < .05). Dietary lipid levels affected serum biochemical parameters, with the highest AST, TC, LDL‐C and LDL‐C/TC in L21 or L25 group and highest HDL‐C in the L17 group. Serum antioxidants, oxidants and liver MDA content maintained upward trends with increasing dietary lipid from 51.1 to 248.8 g/kg ( p < .05). Lipase activity in the spiral valve intestine increased when dietary lipid rose from 51.1 to 169.3 g/kg, but declined when lipid level up to 208.4 and 248.8 g/kg ( p > .05). To sum up, the optimal dietary lipid was 169.9–176.0 g/kg for juvenile Acipenser baerii .